The role of power and kinetic asymmetry in differentiating elite vs. sub-elite wheelchair rugby sprint performance - O'Brien, T. J.; Briley, S. J.; Murphy, C.; Goosey-Tolfrey, V. L. (Journal of Sports Sciences, 2025)
Wheelchair sprint performance varies by sports classification. Yet, it is unclear how spatio-temporal, kinetic and kinetic asymmetries of wheelchair sprinting differ among wheelchair rugby players of different performance standard. The study purpose was to examine the associations between 30s sprint performances and spatio-temporal, kinetic and kinetic asymmetries on a dual-roller ergometer in elite and sub-elite wheelchair rugby players (n = 20). Kinetic differences between groups were investigated using statistical parametric mapping. Peak velocities were associated with the acceleration phase and higher peak power (r = 0.62, p = 0.003) and lower push times (r=-0.50, p = 0.020). Greater distance travelled during the acceleration phase were correlated with lower asymmetries in peak power (r=-0.58, p = 0.005). Overall, both peak velocity and total distance covered during the entire sprint was correlated with lower push times (r=-0.61, p = 0.003 and r=-0.62, p = 0.003) but greater peak power (r=-0.61, p = 0.003 and r=-0.62, p = 0.003). Elite players had lower power asymmetries between 1 to 15% and 95 to 100% of the push phase during the acceleration phase, accompanied by a lower initial contact asymmetry (p = 0.011). While power is an essential feature of sprinting, our findings show that how it is applied, in terms of asymmetry and coordination might differentiate the performance in wheelchair rugby.